Bahasa Inggris - Syarifudin Rahim; Mindy Eka Astuti; Syam S Kumaji (LPPM Universitas Bina Mandiri Gorontalo, 2020)
The purpose of this study was to determine the results of the analysis of Coliform bacterial contamination in tomato sauce snacks on Jalan Toto Tengah, Gorontalo City.This research method is descriptive observational with a qualitative approach. The method in this study uses the MPN method which consists of the estimator test, reinforcement test and Gram staining and uses the MPN 333 table according to Thomas's formula.The results showed that all samples of tomato sauce tested positive for Coliform bacteria and did not meet the standards based on BPOM Standard number HK.00.06.1.52.4011 in 2009 concerning the maximum limit of microbial and chemical contamination in food with a maximum APM Coliform of 100 APM/g. estimator test all samples change color to yellow. Meanwhile, in the reinforcement test results, 1 sample had metallic green bacterial colonies and 5 other samples had pink colonies and for Gram staining, rod-shaped Gram negative bacteria were obtained.